The Role Of Sharia Economic Ethics In Sustainable Production - Wati; Malik Sofy; Ahta Abdul Mursyid Husni Mubarok (P3M - STAI Kuningan, 2024)
This study aims to analyze the role of Islamic economic ethics in guiding production practices that align with Islamic values, focusing on key principles such as justice, honesty, responsibility, and sustainability. Employing a qualitative approach with a literature study method and normative analysis of primary sources including the Qur'an, Hadith, and scholarly perspectives, this research examines the ethical foundations that govern production activities in Islamic economics. The findings indicate that the application of Islamic ethics encourages morally responsible business behavior, ensuring a balance between material objectives and spiritual values. Furthermore, integrating these ethical principles into production practices promotes fairness, transparency, and accountability, while supporting environmental and social sustainability. The study concludes that Islamic economic ethics play a vital role in fostering equitable and sustainable economic growth, contributing to societal welfare and long-term economic stability. This research offers valuable insights for policymakers, business practitioners, and academics by highlighting the significance of Islamic ethics as a comprehensive framework for ethical production that balances profit-making with social and environmental responsibility.